DOMINANT FACTORS OF JAKARTA’S THREE LARGEST FLOODS - Aldrian, Edvin (Jurnal Hidrosfir Indonesia, 2008)
In year 2002, 2007 and 2008 Jakarta experienced heaviest flood in early February from rain that precipitate in several days ahead. Those rainfalls take place in early morning for few consecutive days. The extreme early morning rainfall occurs due to three dominant phenomena the Madden Julian oscillation wet phase, the cold surge and a vortex in the southwest of Java. The cold surge from north compressed the air mass over the north of Jakarta Bay, picked up as much as water vapor over it and brings to the bay. Especially at night during intense land breeze, south ward movement of compressed and moist air collided frontally with the land breeze andcaused strong uplifting at the coast. The latter phenomenon created strong convection at the Jakarta metropolitan areas at early morning and caused extreme rainfall events. Those daily rainfall rate are almost and exceed the monthly rainfall values. Analises of data from satellite observation, rain gauge, wind and radar imagery prove the mechanism of extreme weather in early morning that cause heavy flood over Jakarta. The incoming of those three phenomena could be predicted in advance with quite a certainty. The MJO is a feature that has 50 days oscillation so that MJO wet phase could be predicted in advance up to 2 weeks. The cold surge that comes from Siberia has index of sudden drop of pressure in Hongkong before propagate to Southeast Asia, thus could be predicted in advance about one week ahead. Lastly the vortex development in southwest of Java could be predicted up to 1 days in advanced. Those information on the three major or dominant weather feature will be a good early warning for heavy flood of Jakarta especially in early February.